Medial versus Posterior Triceps Splitting Approach in Open Reduction Internal Fixation of Displaced Supracondylar Fracture of Humerus - Rokaya, Poojan K; Karki, Dhan Bahadur; Rawal, Mangal; Limbu, Deoman; Khan, Javed Ahmed; Bhandari, Prakash Raj; Ghimire, Anil; Sharma, Rachit; Shrestha, Niraj Man (Journal of Nepal Health Research Council, 2020)
Background: The purpose of this study is to compare the clinical and radiological outcome of medial versus posterior triceps splitting approach in open reduction internal fixation of displaced supracondylar fracture of humerus in children.Methods: A retrospective review of total 70 children with medial approach (n=30) and posterior triceps splitting approach (n=40) children was made. Time to radiological union, postoperative Bauman’s angle and Lateral humerocapitellar angle was compared for radiological outcome. Cosmetic and functional outcome was assessed and compared using Flynn’s criteria. Results: Radiological parameters like time to union, postoperative Bauman’s angle and Lateral humerocapitellar angle were similar and non-significant between medial and posterior triceps splitting approach. Flynn’s cosmetic outcome was similar between these approach (p=0.198). Loss of ROM was significant in posterior triceps splitting approach (p=0.00). Flynn’s functional outcome was better with medial approach as compared to posterior triceps splitting approach with statistical significance (p=0.00). Conclusions: Medial approach has better functional outcome compared to posterior triceps splitting approach in open reduction internal fixation of displaced supracondylar fracture of humerus in children.Keywords: Children; Humerus; Open reduction; Supracondylar